Glacial landforms as geodiversity resources for geotourism in Tierra del Fuego, Argentina - Coronato, Andrea; Schwarz, Soledad; Flores Barrera, Flavia (Quaestiones Geographicae, 2022)
The southern extreme location and the natural landscapes, highly modelled by glaciers during the Quaternary period, give Tierra del Fuego a unique opportunity to attract visitors worldwide. Its glacial landforms are geodiversity resources that are witness to global climate changes as natural processes. Therefore, this study aims to highlight different glacial landforms considering their geodidactic potential for educational information in terms of geographical study. Sixteen georesources connected by routes are analysed, using bibliographic research, fieldwork and a datasheet designed ad-hoc. Four of them were formed during middle Pleistocene glaciations and the other twelve during the Last Glacial Maximum (LGM), out of which two also represent the Holocene, which happens to be the youngest glaciation.